2015
DOI: 10.1002/cbf.3110
|View full text |Cite
|
Sign up to set email alerts
|

Tumour promotion versus tumour suppression in chronic hepatic iron overload

Abstract: Although iron-catalysed oxidative damage is presumed to be a major mechanism of injury leading to cirrhosis and hepatocellular carcinoma in hemochromatosis, these events have been difficult to recapitulate in an animal model. In this study, we evaluated regulators of hepatocarcinogenesis in a rodent model of chronic iron overload. Sprague-Dawley rats were iron loaded with iron dextran over 6 months. Livers were harvested and analysed for markers of oxidative stress, as well as the following proteins: p53, muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Liver tissue was homogenized in RIPA buffer (50mM Tris, 150mM NaCl, 0.25% sodium deoxycholate, 1% triton‐X, 1mM EDTA, 1mM Na 3 VO 4 ), and the protein concentration of each sample was determined by the Bradford protein assay (BioRad, Hercules, California). Immunoblotting was performed as previously described . Primary antibodies were obtained from the following sources: Sigma, St Louis, Missouri (ferritin; F5012); Santa Cruz Biotechnology, Santa Cruz, California (divalent metal transporter‐1 [DMT‐1]; SC30120); and Alpha Diagnostics International, Inc, San Antonio, Texas (ferroportin [Fpn]; MTP11‐S).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver tissue was homogenized in RIPA buffer (50mM Tris, 150mM NaCl, 0.25% sodium deoxycholate, 1% triton‐X, 1mM EDTA, 1mM Na 3 VO 4 ), and the protein concentration of each sample was determined by the Bradford protein assay (BioRad, Hercules, California). Immunoblotting was performed as previously described . Primary antibodies were obtained from the following sources: Sigma, St Louis, Missouri (ferritin; F5012); Santa Cruz Biotechnology, Santa Cruz, California (divalent metal transporter‐1 [DMT‐1]; SC30120); and Alpha Diagnostics International, Inc, San Antonio, Texas (ferroportin [Fpn]; MTP11‐S).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was performed as previously described. 27 Primary antibodies were obtained from the following sources: Sigma, St Louis, Missouri (ferritin; F5012); Santa Cruz Biotechnology, Santa Cruz, California (divalent metal transporter-1 [DMT-1]; SC30120); and Alpha Diagnostics International, Inc, San Antonio, Texas (ferroportin [Fpn]; MTP11-S).…”
Section: Immunoblotsmentioning
confidence: 99%
“…The intensity of staining was quantified with Image lab, and the band density of the protein of interest was normalized to the intensity of the Ponceau stain. We and others have shown that protein abundance on nitrocellulose membranes is better quantified with Ponceau staining compared to routine protein loading controls such as beta-actin [ 14 , 15 ]. Results were further normalized to the adult male control diet group, which was given a value of 1.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to the commonly held view of iron as hepatotoxic, there are numerous examples of iron inducing protective responses in the liver, including the upregulation of ferritin, heme oxygenase-1, gamma glutamylcysteine synthetase, cysteine, thioredoxin1, NAD(P)H:quinone oxidoreductase, and tumor suppressor proteins [54,80,87,88].…”
Section: Iron As a Hormetic Agentmentioning
confidence: 99%